Pendidikan Kesehatan Meningkatkan Tingkat Pengetahuan dan Sikap Ibu dalam Merawat Balita dengan ISPA - Dewi Purnama Sari; Diah Ratnawati (UIMA Press, 2020)
Abstract Introduction : Health education is a series of influencing someone to create healthy living behavior. Public health counseling is an educational activity carried out by disseminating messages, to the community so that the community is aware, knows, understands, wants, and can take actions that are related to health. Purpose :The purpose of this report to determine the effect of health education on the level of knowledge and attitudes in mothers of children under five in caring for children with Acute Respiratory Infection at Integrated Health Center Kelurahan Limo. Method: This research method uses quasi-experiment and data analysis using a t-test dependent test. The sample was 53 respondents who had a child aged one to five years at Integrated Health Center Kelurahan Limo with a purposive sampling method. Results: The results showed that there was a significant effect between health education on the level of knowled and the attitude of mother in caring for children with Acute Respiratory Infection Conclusion: This shows that health education has a significant influence on the knowledge and attitude of a mother with a toddler about Acute Respiratory Infection at Integrated Health Center Kelurahan Limo.